Developing insights into the link between art and tourism through the value co-creation lens. (22nd August 2020) - Gökbulut Özdemir, Özge; Fillis, Ian; Baş Collins, Ayşe
Abstract : Purpose: The aim of the study is to gain insight into the link between art and tourism from a value co-creation perspective. This link is discussed with the help of the arts marketing, art tourism and value co-creation literature. The role of art in tourism and the role of cultural places in arts marketing are also evaluated. Design/methodology/approach: Focussing on two cultural heritage sites in Turkey, Zeugma and Göbeklitepe, a qualitative study was undertaken in order to determine the value creation and co-creation processes occurring from the art–tourism contexts based on comparative case study analysis. In-depth semi-structured interviews were conducted with three groups of actors. Motivation, expectation and stakeholder experiences were the main themes explored. Findings: The findings of the study relate to the role of the co-creation process. Marketing art in alternative places creates value in closing the gap between art and society through the use of related fields such as culture and heritage. In terms of cultural value, the paper identifies the reconnection with cultural heritage through contemporary art. This is a way of looking at culture and its concepts in different time and place dimensions which make visitors more engaged with culture and its contemporary reflection through art. Research limitations/implications: Although the research focusses on two Turkish art and tourism cases, future research can be extended to other countries, including the assessment of the longer-term role of similar activities. Practical implications: As art is a subset of culture, the people who are interested in culture and history also have the potential to be interested in art. While art impacts on cultural tourism, cultural heritage and tourism work as arts marketing tools in a co-supporting way. The coming together of art and culture has societal benefits. There are lessons for practice such as the opening of a space for contemporary art in cultural heritage museums in order to promote art to society. The museum audience is an important potential for the future of art from a market generation perspective. Originality/value: The study contribute to arts tourism, arts marketing and value co-creation in theory and practice.